Antihistamine Potential of Red Alga Acanthophora spicifera Through Combination In Vivo, In Vitro, and In Silico Study - Wahyuni, Ilmi; Soekamto, Nunuk Hariani; Rasyid, Herlina; Annisa, Nurul; Adriana, Risda; Putri, Alifiah Alfaniah Alfattah; Basir, Djabal Nur; Ahmad, Ahyar; Fauziah, St.; Irfandi, Rizal (Indonesian Journal of Chemistry, 2026)
Red alga Acanthophora spicifera is a marine species with potential as a source of natural antihistamines. This study evaluated the bioactivity of its secondary metabolites through in vivo, in vitro, and in silico approaches. Extracts were obtained by successive maceration using n-hexane, ethyl acetate, and methanol. In vivo testing on BALB/c mice showed that extract administration did not cause significant weight loss. However, its effect on allergic symptoms was significant (p < 0.05), with the methanol extract identified as the most effective by the Mann–Whitney test. In vitro assays revealed a significant reduction in histamine levels (p < 0.05) during sensitization, treatment, and post-challenge phases, particularly in the methanol extract group. In silico docking demonstrated that two compounds from the methanol extract exhibited strong binding affinity to the H1 receptor (PDB ID: 3RZE), with binding energies of −6.27 and −5.06 kcal/mol. These findings suggest that A. spicifera, particularly its methanol extract, is a promising source of natural antihistamines with potential applications in the development of safer allergy treatments.